A review on the diverse interactions between microalgae and nanomaterials: Growth variation, photosynthetic performance and toxicity. (May 2022) - Lau, Zhi Lin; Low, Sze Shin; Ezeigwe, Ejikeme Raphael; Chew, Kit Wayne; Chai, Wai Siong; Bhatnagar, Amit; Yap, Yee Jiun; Show, Pau Loke
Graphical abstract: Highlights: This review comprehensively discusses diverse interactions of microalgae-NMs. Low NMs concentration aids microalgal growth, photosynthesis (hormetic response). High NMs concentration damages photosynthetic proteins and adversely impacts growth. Nanobionic improves photosynthesis due to NMs localization in chloroplast. Nanoceria and CNT in microalgae promote growth while removing adverse effect. Abstract: Vast improvements in nanotechnology have led to the wide usage of nanomaterials (NMs) in daily products. This study reviews the interactions between NMs and microalgae in terms of impacts on growth and photosynthetic efficiency, and their toxicity on microalgae. All types of NMs such as carbon-based NMs (CNMs), metal oxide-based NMs (MONMs) and noble metal-based NMs (NMNMs) improve microalgal growth and photosynthetic efficiency at low concentration, typically ranging between 1 and 15 mg/L depending on the type of NMs, due to hormetic responses by microalgae. Higher concentrations of NMs have been found to reduce photosynthetic efficiency and subsequent growth inhibition of microalgae. MONMs-microalgae and NMNMs-microalgae interactions focus on membrane alteration, whereas carbon-based NMs-microalgae focus more on shading effect. The toxicity of each type of NMs on microalgae is in the order rGO > GO > MG > CNT for carbon-based NMs, ZnO > TiO2  > CuO > Fe2 O3 for MONMs and Ag > Au > Pt for NMNMs. Incorporation of NMs in microalgae are seen to have promising future on producing higher microalgae yield with increased economic efficiency.